Prospective comparison of perioperative antibiotic management protocols in oncological head and neck surgery. Issue 7 (July 2017) - Bartella, Alexander K.; Kamal, Mohammad; Teichmann, Jan; Kloss-Brandstätter, Anita; Steiner, Timm; Hölzle, Frank; Lethaus, Bernd
Abstract: Objectives: The adequate perioperative antibiotic prophylaxis in head and neck cancer surgery is an important and easy applicable tool to decrease nosocomial morbidity and mortality by reducing the rate of infections. In the study a strictly perioperative antibiosis is compared with an extended postoperative prophylactic antibiosis. We aim to clarify the value of postoperative prophylactic antibiosis for the recovery and clinical course of patients. Material and methods: In this prospective study 75 consecutive patients, who underwent major oncological head and neck surgery were included and divided in three groups, each containing 25 patients. The first group received peri- and postoperative antibiotic prophylaxis (POAP) from the day of operation until the fifth day postoperatively. The second group was treated with perioperative antibiotic prophylaxis (PEAP) only. The third group received perioperative antibiotic prophylaxis and increased local antiseptic care (PAPAC). General anamnestic data was collected, as well as duration of hospitalisation, stay on intensive care unit, rate and type of infections, surgical closure of the tracheostomy, and postoperative blood parameters. Results: There were no statistically significant differences in general diseases or extent of surgery between the groups. There were statistically significant fewer patients suffering from surgical site infections in subjects with POAP (n = 1) in comparison to PEAP (n = 9; p = 0.011) and PAPAC (n = 9; p = 0.011). In contrast, other nosocomial infections (pneumonia, urinary tract infection, sepsis) did not decrease under a prolonged antibiotic prophylaxis. Conclusion: Based on findings of the study, we recommend an extended postoperative antibiotic prophylaxis for patients undergoing major oncological head and neck surgery.